1969
DOI: 10.1139/y69-064
|View full text |Cite
|
Sign up to set email alerts
|

The exchange of glucose across the liver cell membrane

Abstract: A set of equations was worked out to estimate the rapidity of the outward penetration of glucose from the hepatic intracellular compartment into the plasma compartment. In dynamic steady states at different blood sugar levels the average rate constant was found to be 0.46 min−1. Thus the rate at which glucose leaves the liver cell is rapid, but not instantaneous. The flux rates of glucose across the liver cell membrane were calculated and were found to be approximately eight times higher than the rate of gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1969
1969
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The mean ECF fraction of the total liver water was 0.46, which is similar to that reported by Hetenyi et al (29).…”
Section: Icf Fraction = Total Liver Water -Ecf Fractionsupporting
confidence: 90%
“…The mean ECF fraction of the total liver water was 0.46, which is similar to that reported by Hetenyi et al (29).…”
Section: Icf Fraction = Total Liver Water -Ecf Fractionsupporting
confidence: 90%
“…Our modeling of glucose exchange has not taken this additional process into account. We have not incorporated into the modeling the effect of this added flux, the addition of unlabeled glucose to the intracellular space (24). Its addition would complete the modeling so that it would then correspond more accurately to the processes underlying glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Some non-metabolized analogues of D-glucose, 3-0-methyl glucose and L-glucose, also distribute in a similar intracellular volume (Hetenyi, Norwich, Studney & Hall, 1969). Mediation of monosaccharide transfer by a membrane component is suggested by the finding that L-glucose enters the cells of the isolated perfused liver of the rat very slowly, and that this transfer is inhibited by D-glucose (Williams, Exton, Park & Regen, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…From work with liver slices in vitro (Berthet, Jacques, Hers & DeDuve, 1956) and with perfused rat livers (Hetenyi & Arbus, 1962;Hetenyi, Kopstick & Retelstorf, 1963), it has been concluded that D-glucose equilibrates rapidly between the cell water and the extracellular medium. Some non-metabolized analogues of D-glucose, 3-0-methyl glucose and L-glucose, also distribute in a similar intracellular volume (Hetenyi, Norwich, Studney & Hall, 1969). Mediation of monosaccharide transfer by a membrane component is suggested by the finding that L-glucose enters the cells of the isolated perfused liver of the rat very slowly, and that this transfer is inhibited by D-glucose (Williams, Exton, Park & Regen, 1968).…”
Section: Introductionmentioning
confidence: 99%